Analysis of HR Development on HR Competency and Performance Mediated by Readiness for Change in The Era of Industrial Revolution 4.0 - Ananto Pramandhika; Intan Ratna Wati (International Journal of Economics Development Research (IJEDR), 2024)
The Industrial Revolution is a condition that has an impact on various areas of life caused by global change. In the Industrial Era 4.0, cyber technology is combined with automatic technology. The implementation concept focuses on the concept of automation that technology carries out which in the end can minimize or even eliminate individual labor. The research problem is how to improve HR competency and performance through HR development and readiness for change. The aim of this research is to analyze the influence of HR development on readiness for change in improving HR competency and performance. The sample for this research is employees of PT. Indofood CBP Sukses Makmur, Tbk. Semarang Branch Instant Noodle Division, a total of 203 respondents. SEM analysis with AMOSS software was used to analyze the data. The results of the analysis showed that human resource development had an effect on readiness for change in increasing competence and readiness for change. These empirical findings indicate that human resource development has a significant positive effect on competence; HR development has a significant positive effect on HR performance; HR development has a significant positive effect on readiness for change; readiness for change has a significant positive effect on competency and readiness for change has a significant positive effect on HR performance.